2023
DOI: 10.1017/s0021859624000029
|View full text |Cite
|
Sign up to set email alerts
|

Yield and nutritive value of Stylosanthes spp. genotypes subjected to different harvest frequencies and seasons of the year

W. P. S. Diniz,
M. V. F. Santos,
M. V. Cunha
et al.

Abstract: Productive and nutritional traits of forage species in various regions worldwide depend on different management strategies. This study aimed to evaluate the effects of harvest frequency (56, 77 and 98 days) and season of the year (rainy and dry) on the nutritional value and fractionation of carbohydrates and proteins of Stylosanthes genotypes (S. seabrana, S. scabra, S. mucronata and Stylosanthes spp. cv. Campo Grande). The experiment was conducted using a randomized complete block design with a split-plot arr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Beelen et al 2006). Diniz et al (2024) evaluated the nutritional value of Stylosanthes spp. a subshrub legume, and reported that the highest concentration of condensed tannins occurred in the dry period since the biosynthesis of condensed tannins is related to environmental conditions.…”
mentioning
confidence: 99%
“…Beelen et al 2006). Diniz et al (2024) evaluated the nutritional value of Stylosanthes spp. a subshrub legume, and reported that the highest concentration of condensed tannins occurred in the dry period since the biosynthesis of condensed tannins is related to environmental conditions.…”
mentioning
confidence: 99%